The Harsanyi value for nontransferable utility games with restricted cooperation. (3rd June 2018) - Gallardo, J. M.; Jiménez, N.; Jiménez-Losada, A.
Abstract: A nontransferable utility (NTU) game assigns a set of feasible pay-off vectors to each coalition. In this article, we study NTU games in situations in which there are restrictions on coalition formation. These restrictions will be modelled through interior structures, which extend some of the structures considered in the literature on transferable utility games for modelling restricted cooperation, such as permission structures or antimatroids. The Harsanyi value for NTU games is extended to the set of NTU games with interior structure.